PERANG SALIB (Tinjauan Kronologis dan Pengaruhnya terhadap Hubungan Islam dan Kristen) - Abidin, Zaenal (RIHLAH, 2013)
The Crusades happened because of two factors; due to internal conflicts Europe, namely the dualism Christian denominations; namely the Roman Catholic church with its Eastern Orthodox church with its Byzantine Constantinople, and because of the hatred and fear of Muslims to control their existence. Christian-Muslim relations after the Crusades, it can be said better . Both sides can understand each other and show tolerance and efforts to improve inter-religious harmony , but underneath all of that is still common friction and tension between the two sides . Conflicts with religious issues are considered by some as the shadow and influence of